Index to Studia Aethiopica - Böll, Verena; Nosnitsin, Denis; Rave, Thomas; Smidt, Wolbert G.C.; Sokolinskaia, Evgenia (Aethiopica, 2005)
Index to Verena Böll, Denis Nosnitsin, Thomas Rave, Wolbert Smidt and Evgenia Sokolinskaia (eds.), Studia Aethiopica. In Honour of Siegbert Uhlig on the Occasion of his 65th Birthday, Harrassowitz Verlag: Wiesbaden 2004, 459 pp.